A comparative evaluation of freeze dried bone allograft and decalcified freeze dried bone allograft in the treatment of intrabony defects: A clinical and radiographic study - Rajat Gothi; Mansi Bansal; Mayur Kaushik; Braham Prakash Khattak; Nikhil Sood; Vishal Taneja (Wolters Kluwer Medknow Publications, 2015)
Background: Ideal graft material for regenerative procedures is autogenous bone graft but the major disadvantage with this graft is the need for a secondary surgical site to procure donor material and the frequent lack of intraoral donor site to obtain sufficient quantities of autogenous bone for multiple or deep osseous defects. Hence, to overcome these disadvantages, bone allografts were developed as an alternative source of graft material. Materials and Methods: In 10 patients with chronic periodontitis, 20 bilateral infrabony defects were treated with freeze dried bone allograft (FDBA-Group A) and decalcified freeze dried bone allograft (DFDBA-Group B). Clinical and radiographic parameters were assessed preoperatively and at 3 months and 6 months postoperatively. Data thus obtained was subjected to statistical analysis. Results: Significant improvement in the reduction in probing depth and relative attachment level (RAL) from the baseline to 3 months to baseline to 6 months in group A and group B, which was statistically significant but no statistically significant reduction was seen between 3 months and 6 months. On inter-group comparison, no significant differences were observed at all-time points. In adjunct to the probing depth and RAL, the radiographic area of the defect showed a similar trend in intra-group comparison and no significant difference was seen on inter-group comparison at all-time points. Conclusions: Within the limitations of the current study, it can be concluded that DFDBA did not show any improvement in the clinical and radiographic parameters in the treatment of the intrabony defects as compared to FDBA.